Revisión Documental Sobre Recursos Psicológicos en el Manejo del Estrés - Olaya Rojas, Brighit (Universidad Antonio Nariño, 2022)
The main objective of this research was to identify in the academic literature the characteristics and types of psychological resources that help people to manage stress, through a systematic review of the research carried out in the last ten years according to the established procedures. in the precepts of the PRISMA declaration for conducting systematic reviews